2001
DOI: 10.1097/00008390-200108000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and carboplatin combination as second-line chemotherapy in dacarbazine-resistant melanoma patients

Abstract: High-dose cisplatin regimens have been shown to be highly active in advanced melanoma patients but are associated with unacceptable side effects. In order to increase the platinum dose but avoid severe side effects, we treated 15 dacarbazine (DTIC)-resistant metastatic melanoma patients with a combination regimen of cisplatin (100 mg/m2) and carboplatin (200 mg/m2), two platinum analogues with a similar mode of action but a different toxicity pattern. After a mean follow-up period of 10.7 months (range 4-18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 10 publications
1
22
0
3
Order By: Relevance
“…We found 50% of the patients with SD. Comparable results with this therapeutic regimen have been reported by Guven et al [16] with objective response rates of 26% and a median survival of 7.1 months. Their results in conjunction with our independent confirmation in a much larger group of patients seem to indicate a beneficial effect for the combination of cisplatin and carboplatin.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We found 50% of the patients with SD. Comparable results with this therapeutic regimen have been reported by Guven et al [16] with objective response rates of 26% and a median survival of 7.1 months. Their results in conjunction with our independent confirmation in a much larger group of patients seem to indicate a beneficial effect for the combination of cisplatin and carboplatin.…”
Section: Discussionsupporting
confidence: 71%
“…In a small study, the combination of cisplatin and carboplatin was well tolerated and showed favourable response rates and a possible impact on overall survival in dacarbazine-resistant patients with disseminated melanoma [16] . Second-line studies are needed, but are rare in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The goal in developing new metal-based anticancer drugs is to overcome the main limitations of cisplatin, such as its narrow range of activity, the development of resistance, and its severe toxicity. [5] Apoptosis is the basic mechanism of the anticancer action of numerous chemotherapeutics.…”
mentioning
confidence: 99%
“…Platinum compounds, which cross-link DNA, are considered to be among the more active cytotoxic chemotherapeutics in melanoma [17]. Sunitinib inhibits receptor tyrosine kinases, which signal through several pathways, including the MAPK pathway.…”
Section: Current Approachesmentioning
confidence: 99%